2014
DOI: 10.1155/2014/285607
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes of Virulent and NonvirulentEntamoeba histolyticaStrains Identified by Suppression Subtractive Hybridization

Abstract: Entamoeba histolytica is a parasite which presents capacity to degrade tissues and therefore has a pathogenic behavior. As this behavior is not shown by all strains, there have been several studies investigating molecular basis of the cytotoxicity process. Using the suppression subtractive hybridization (SSH) technique, differential gene expressions of two E. histolytica strains, one virulent (EGG) and one nonvirulent (452), have been analyzed with the purpose of isolating genes which may be involved with amoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Molecular studies have disclosed a high degree of genetic polymorphism among strains of E. histolytica (246). Researchers have studied variation in genetic expression between virulent and avirulent strains to better understand the disease process (247). Perhaps most interesting, Jaiswal and colleagues studied the allelic variation in E. histolytica and correlated this with the clinical phenotypes of amebiasis (e.g., patients with dysentery versus asymptomatic cyst passers) and found correlations between certain alleles and disease states (248).…”
Section: Laboratory-developed Tests For Gastrointestinal Parasites Mmentioning
confidence: 99%
“…Molecular studies have disclosed a high degree of genetic polymorphism among strains of E. histolytica (246). Researchers have studied variation in genetic expression between virulent and avirulent strains to better understand the disease process (247). Perhaps most interesting, Jaiswal and colleagues studied the allelic variation in E. histolytica and correlated this with the clinical phenotypes of amebiasis (e.g., patients with dysentery versus asymptomatic cyst passers) and found correlations between certain alleles and disease states (248).…”
Section: Laboratory-developed Tests For Gastrointestinal Parasites Mmentioning
confidence: 99%
“…However, there is no evidence in support of these activities. Recent studies have suggested the involvement of grainin 2 in amebic virulence because it was found to be present differentially in virulent organisms [63]. EhCaBP2 displays 79% sequence identity with EhCaBP1 and also has 4 Ca 2+ -binding EF-hand domains [66] (Fig 2).…”
Section: Other Cabpsmentioning
confidence: 99%
“…[ 63,64] EhCaBP7-27 Other calcium-binding proteins encoded in the E. histolytica genome. Function is not deciphered yet.…”
Section: Ehcabp6mentioning
confidence: 99%
“…Comparison of the transcriptome of highly virulent HM-1: IMSS and less virulent Rahman strain highlighted lower expression of 32 genes, including cysteine proteinases, AIG family members and lasting light chains. Thus, one possible explanation for the differential outcome of disease may be that a single gene product is not responsible, but rather multiple pathways 37 . Additionally, small RNA pyrosequencing indicates that small RNA population may contribute differential gene expression between virulent and nonvirulent strains 38 .…”
Section: Strain Variation and Its Detectionmentioning
confidence: 99%